TRANSFORMAÇÕES ADAPTATIVAS EM CONTEÚDOS DE GEOMETRIA ANALÍTICA: UM ESTUDO DE CASO ENVOLVENDO TRANSPOSIÇÃO DIDÁTICA - Afonso, Reginaldo Fabiano da Silva (2021)
This is a study on the adaptations of specific syllabus made by a teacher, which are expected to be developed in curricular components of a given higher education institution. The interest in this subject came to light due to the teaching practice and also due to the observation, via research called “state of knowledge”, that the Didactic Transposition applied to the teaching of Analytical Geometry at a higher level appears as a possible niche for investigation. The theoretical foundation is built according to the concepts of Didactic Transposition and Didactic Situations. In order to discuss how these two factors influence the didactic relationships established in the didactic system, it was proposed a qualitative research consisting of document analysis and experimental investigation. The first seeks to describe the mathematical organizations and didactic organizations presented in the books that make up the basic bibliography of an undergraduate course offered by a higher education institution in relation to 'knowing how to teach' conic, given that this skill Pedagogical comes as a structuring element of scientific knowledge. The second seeks to understand how the implementation of the phases of Didactic Situations can influence the learning process of knowing how to teach conics through interdisciplinary activities. For this, two activities were proposed in line with the profile of graduates of the Environmental and Sanitary Engineering Course, with the regional reality and with the mathematical concepts of conics, which were developed during 12 virtual meetings. Data collection was carried out through filming, audio recording and collection of written records produced during the activities. The first aimed to identify the gestures and levels of involvement of students in the activities proposed by the researcher; the second sought to describe the verbal expressions used in that situation and how they show the different viewpoints of the participants; and the third allowed the group's mathematical and didactic organizations to be analyzed. The research was applied to Environmental and Sanitary Engineering Course students regularly enrolled at the Federal University of Pampa/Campus Caçapava do Sul, who were interested and also available to participate in the voluntary monitoring program, in the research modality.